Mutation analysis of apyrase gene of Shigella Flexneri- towards the development of vaccine strain - Aun, Seah Chin (2005)
The discovery of the microbe Shigella was dated back about 100 years ago by a scientist named Kiyoshi Shiga. Virulent Shigella spp. are known to cause bacillary dysentery (shigellosis) in humans which is characterized by the passage of bloody stools. According to the WHO, an estimated of 1.1 million global population dies every year is due to the disease shigellosis. Despite much studies were carried out regarding this pathogenic bacteria, no vaccine is available for this infectious disease. Literatures have postulated that one of the virulence genes is the apy gene which encodes for apyrase. Therefore, in this study the gene of interest is the apy gene. We have successfully mutated the apy gene with a kanamycin gene cassette (aphA) and subcloned the construct into a conjugative suicide vector. The use of this antibiotic gene cassette is to facilitate the process of manipulating the genes as it serves as a selective marker. The creation of the construct (apy::aphA) is to facilitated the approach into the development of a potential vaccine strain of Shigella; as literatures have indicated that apy gene is one of the virulence genes. Furthermore, mutation of the virulence genes has been proven to be highly immunogenic and safe.